Feeding the high producing cow - D. J. Schingoethe (Kansas Agricultural Experiment Station Research Reports, 1993)
Dairy cows must consume a lot of feed to achieve the levels of production expected today; however, the nutrient needs of dairy cows vary immensely between the dry period and peak lactation. Requirements for the former often can be met with forages alone, whereas the latter may require a considerable amount of high-energy feeds such as grains and supplemental fat and ruminally undegradable proteins of good quality that are digestible in the gastrointestinal tract. The challenge for a dairy feeding program is to meet the cow's nutrient needs while minimizing body weight loss, not causing digestive upsets, and maintaining health.; Dairy Day, 1993, Kansas State University, Manhattan, KS, 1993;
Keywords: Dairy Day; 1993; Kansas Agricultural Experiment Station contribution; no. 94-149-S; Report of progress (Kansas Agricultural Experiment Station); 694; Dairy; Cows; Lactating; Feeding; Energy; Protein